Peningkatan Pengetahuan Cara Merawat Gigi Sehat pada Siswa-Siswi TK Wadi Fatimah - Yani Trihandayani; Lisa Rahmawati; Vinne Maharani; Fidela Nurul Janitra; Clarisa Ayu Amanta; Inesya Azzahra Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Early childhood dental health is a crucial issue that requires serious attention, given the high prevalence of dental caries which is influenced by various factors, including inadequate brushing habits and excessive consumption of sugary foods. This Community Service aims to analyze in depth the correlation between the level of parental knowledge about dental health, brushing practices in children, and sweet food consumption patterns to the incidence of dental caries in Wadi Fatimah Kindergarten (TK). The Community Service Method applied is observational analysis with a cross-sectional design, involving 64 early childhood children as participants. The results of Community Service revealed that 62.5% of children have dental caries, an alarming number. Of these, 53.1% of children showed improper brushing habits, while another 54.7% of children often consumed sweet foods. Furthermore, this Community Service also highlights that only 39.1% of parents have a good understanding of dental health, while the rest still need more comprehensive education. It is important to remember that children's dental health is a shared responsibility between parents, educators, and the community. With a good understanding of the importance of maintaining dental health from an early age, as well as support from various parties, it is hoped that children can grow up with healthy and strong teeth, which will ultimately improve their overall quality of life.